2006
DOI: 10.1093/geront/46.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Home Staffing Standards: Their Relationship to Nurse Staffing Levels

Abstract: State staffing standards may not be effective policy tools because they are only one of many factors that affect facility staffing levels. Setting a low minimum HPRD standard may fail to raise staffing, or it may even have a dampening effect on staffing rates in facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 14 publications
5
86
0
Order By: Relevance
“…Harrington (2005aHarrington ( , 2005b found that median nurse staffing levels in nursing homes (3.16 HPRD) are greater than state average minimum standards (2.32 HPRD) for the year 1999 to 2001. Mueller et al (2006), reviewing state staffing standards for the year 2004, found that facilities in states with high staffing standards (above 2.50 total staffing HPRD) have higher staffing levels than states with low (below 2.50 total staffing HPRD) or no staffing standards (adhering to the federal staffing requirements), while there is no significant difference in facility staffing levels among states with low and no staffing standards. A study conducted by Harrington, Swan, and Carrillo (2007) found that state RN staffing standards have positive impact on both RN and total nurse staffing levels.…”
Section: New Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Harrington (2005aHarrington ( , 2005b found that median nurse staffing levels in nursing homes (3.16 HPRD) are greater than state average minimum standards (2.32 HPRD) for the year 1999 to 2001. Mueller et al (2006), reviewing state staffing standards for the year 2004, found that facilities in states with high staffing standards (above 2.50 total staffing HPRD) have higher staffing levels than states with low (below 2.50 total staffing HPRD) or no staffing standards (adhering to the federal staffing requirements), while there is no significant difference in facility staffing levels among states with low and no staffing standards. A study conducted by Harrington, Swan, and Carrillo (2007) found that state RN staffing standards have positive impact on both RN and total nurse staffing levels.…”
Section: New Contributionmentioning
confidence: 99%
“…Chainaffiliated facilities have been reported to have significantly low nurse staffing levels as compared with freestanding ones Mueller et al, 2006;Mukamel et al, 2012). A recent study found that for-profit chains have much lower staffing levels than both nonprofit chains and freestanding facilities .…”
Section: Organizational Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 states have established additional staffing requirements beyond the federal requirements [57]. Research has found that higher state minimum nurse staffing requirements were associated with higher nurse staffing levels [57][58][59] and were generally associated with improved resident outcomes [58,60].…”
Section: Other Regulatory Approachesmentioning
confidence: 99%
“…Research has found that higher state minimum nurse staffing requirements were associated with higher nurse staffing levels [57][58][59] and were generally associated with improved resident outcomes [58,60]. State governments have also sought to improve staffing levels through wage pass-through policy, which required that a portion of Medicaid reimbursement or its increase be directed toward staffing improvements, either through enhanced wages or benefits or increasing the number of staff.…”
Section: Other Regulatory Approachesmentioning
confidence: 99%